Biochar Quality During Slow Pyrolysis from Oil Palm Empty Fruit Bunches and Its Application as Soil Ameliorant - Amsar Maulana; Mimien Harianti; Salma Athiyya; Teguh Budi Prasetyo; Moli Monikasari; Irwan Darfis; Dewi Rezki; Herviyanti Herviyanti (Universitas Sebelas Maret, 2025)
The optimal utilization of oil palm empty fruit bunch (OPEFB) waste holds significant potential for biomass bioconversion via slow pyrolysis, presenting a promising alternative for producing high-quality biochar as a soil ameliorant. This study investigates the effects of slow pyrolysis temperatures (≤ 300 °C) on the physicochemical properties of biochar derived from OPEFB and evaluates its efficacy as a soil ameliorant. This study utilized a completely randomized design (CRD) with three replications across two experiments. The first experiment assessed the effect of slow pyrolysis temperature on the quality of biochar derived from OPEFB, with treatments set at four temperatures (150, 200, 250, and 300 °C) levels. The second experiment evaluated the impact of the selected biochar on the surface charge of oil palm plantation soil, applying biochar at five different doses (0, 20, 40, 60, and 80 tons ha-¹). The potential temperature of 200 °C in slow pyrolysis had a significant effect on the quality of biochar from OPEFB with a yield ratio of 27.84% char; proximate (91.95% volatile matter and 0.81% fixed carbon), cation exchange capacity (CEC) [167.73 cmol(+) kg-1], and macro and micronutrients (e.g., C, N, P, K, Ca, Si, Fe, Cu, Zn, and Mn). The potential of O-H, N-H, C-H, and C=O functional groups of biochar from OPEFB for nutrient availability and absorption efficiency proven by the effect of 40 tons ha-1 biochar from OPEFB which significantly increased 80% of soil surface charge [pH by 0.80; organic matter (OM) composition by 19.8%, CEC by 11 cmol(+) kg-1] and nutrients [0.93% C; 0.04% N; 17.57 ppm P2O5; 0.65 cmol(+) kg-1 K] on Inceptisols.